2000
DOI: 10.1007/s001980050007
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of Bone and Connective Tissue after Orthostatic Bedrest

Abstract: Eight male volunteers were submitted to a 6-week anti-orthostatic bedrest trial followed by a 1-month reambulation period. We prospectively monitored whole-body composition by dual-energy X-ray absorptiometry, bone and connective tissue metabolism by biochemical markers and calcium regulating hormones by 1-84 parathyroid hormone and 1,25-dihydroxyvitamin D(3). Bone mineral density (BMD) did not vary significantly; however, a trend toward an increase in head BMD and a decrease in trunk, lumbar vertebrae and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…Thus, two independent measurements of BMD showed almost identical results. The results observed for DXA in spaceflight are supported by results from bed rest studies, (6,7) in which BMD loss is observed in a model of mechanical unloading that does not involve weightlessness. Furthermore, the total body BMD changes were shown to be significantly correlated with Ca balance, a technique that does not require assumptions regarding body composition.…”
supporting
confidence: 61%
“…Thus, two independent measurements of BMD showed almost identical results. The results observed for DXA in spaceflight are supported by results from bed rest studies, (6,7) in which BMD loss is observed in a model of mechanical unloading that does not involve weightlessness. Furthermore, the total body BMD changes were shown to be significantly correlated with Ca balance, a technique that does not require assumptions regarding body composition.…”
supporting
confidence: 61%
“…These precision measures for DEXA scanning are also similar to those published. 27,28 The prevalence of osteoporosis was investigated from T-scores for BMD at di erent sites. The World Health Organisation (WHO) criteria were used to classify T-scores as normal (41 SD below young adult mean), osteopenic (1 ± 2.5 SD below young adult mean), or osteoporotic (42.5 SD below young adult mean).…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were obtained in another 17-week horizontal bed rest study (Shackelford et al 2004). However, in shorter studies, DXA analysis did not show changes in aBMD (Suzuki et al 1996;Uebelhart et al 2000;LeBlanc et al 1987). In a 90-day HDBR study Rittweger et al used pQCT to measure BMC in a resistive exercise group and the corresponding control group (Rittweger et al 2005).…”
Section: Physiological Adaptationmentioning
confidence: 96%
“…Using these techniques bone turnover markers reflecting the changes in bone formation and bone resorption processes in immobilization become obvious (Baecker et al 2003;Inoue et al 2000;Kim et al 2003;Zerwekh et al 1998;Vico et al 1987;Vico et al 1993;Vico et al 1998;Uebelhart et al 2000;Zerwekh et al 1998).…”
Section: Physiological Adaptationmentioning
confidence: 98%